An Adaptive Local Iterative Method for Fast Calculation of Electrostatic Interactions between Charged Polymers in Dielectric Inhomogeneous System. Issue 4 (8th February 2023) - Lin, Hao; Nie, Zhiji; Shang, Enlong; Dai, Shuyang
Abstract: The motion of charged polymers in the 3D dielectric inhomogeneity system is investigated using a hybrid simulation approach that combines a finite difference method with a Brownian dynamics model (FD‐BD) for the polymer chain. The interface difference scheme of the two‐dielectric model is first derived to achieve a smooth extension of the electrostatic potential values and it is verified that it has a second‐order convergence order. In addition, it is displayed that the local iteration method greatly accelerates the efficiency of calculating the electrostatic interaction forces. However, it is found that the computational efficiency improvement of the traditional local iteration is less significant (about three times) for polymer simulations such as 3D diagonal type. Therefore, a new strategy, the banded local iteration method, is proposed and the simulation results demonstrate that it can better adapt the effects of the deformation of the polymer during its motion, where the computational efficiency is increased by 29 times at most, while the relative error is controlled to less than 5.15e−4. The work can be helpful for accelerating the solution of electrostatic forces under dielectric inhomogeneity, and confer new insights into the optimization of iteration for polymer chains with different geometries in large electrostatic systems. Abstract : The motion of charged polymers in the dielectric inhomogeneous system are studied using a hybrid simulation method combining finite difference method and Brownian dynamics. An interface format with second‐order convergence is derived and propose a local iterative strategy to accelerate the computation of electrostatic interactions, and numerical results show a significant improvement in computational efficiency.